Annual report of the Department of Agriculture (animal husbandry research), 1964/1965 - University of Malawi (1969)
Annual report of animal husbandry research. Discussions and data on calf rearing systems, bull progeny performance testing, forage grazing, rumevite supplementation to arrest weight loss, feeding heifers a high plane of nutrition to obtain earlier breeding, economics of pure maize and maize-made supplements and of finishing cross-bred steers on maize concentrates, early-weaning of cross-breds, water consumption, stall-fed cattle, and creep-feeding of sheep at various research sites in Malawi included.